International Theory at the Margins Neglected Essays, Recurring Themes - Greenwood Onuf, Nicholas (Bristol Studies in International Theory, 2023)
This book brings together thirteen of Nicholas Greenwood Onuf's previously published yet rarely cited essays. They address topics that Onuf, a celebrated international theorist, has puzzled over for decades, prompting him to develop a distinctive perspective on international theory as social theory. Among these topics are the problem of materiality in social construction, epochal change in the modern world and the power of language. Building on the work of giants, from Aristotle and Cicero, Hume and Kant, to Derrida and Foucault, and drawing on diverse contemporary theorists, including Seyla Benhabib, James Der Derian, Johan Galtung, Morton Kaplan, Joseph Nye, James Rosenau, Elaine Scarry and Kenneth Waltz, the book ranges over the margins of the field and settles on issues that have never been put to rest